Shape optimization of generalized developable H-Bézier surfaces using adaptive cuckoo search algorithm. (November 2020) - Hu, Gang; Wu, Junli; Li, Huinan; Hu, Xianzhi
Highlights: The shape of generalized developable H-Bézier surfaces (GDHBS) can be adjusted by changing parameters. Three shape optimization models of GDHBS are presented. An adaptive CS optimization algorithm is applied to the solutions of GDHBS shape optimization models. Some representative and convictive examples are performed. Abstract: The shape optimization design of developable surface is a critical and intractable technique in CAD/CAM and used in many manufacturing planning operations. In this paper, we study shape optimization by using a new cuckoo search (CS) algorithm to promote the development of generalized developable H-Bézier surfaces (or GDHBS, for short). According to the duality between points and planes in 3D projective space, the GDHBS shape optimization problem is formulated as an arc length, energy and curvature variation minimization problem of dual curve, respectively. Then, an adaptive CS optimization algorithm is applied to the solutions of those GDHBS shape optimization models. Finally, we illustrate the effectiveness and performance of the proposed methods by some representative and convictive examples.